Intervención de terapista respiratorio en paciente masculino de 35 años con bronquitis aguda. - Escobar Vera, Tanya Melissa (2022)
The present clinical case study was carried out with a 35-year-old patient who went to the emergency area presenting tachycardia saturation, tachypneic with dyspnea, where he was admitted to the resuscitation area. Acute bronchitis is an inflammation of the lining of the bronchial tubes, which carry air in and out of the lungs. People who have bronchitis often cough up thick and possibly discolored mucus. Bronchitis can be acute or chronic. The symptoms presented by the patients were: cyanosis, dyspnea (respiratory difficulty), cough for more than 15 days of evolution, moderate fever. The objective of this work was to apply respiratory therapy techniques to a 35-year-old patient with acute bronchitis who was admitted with the following vital signs: HR: 110 bpm – FR: 25 rpm – T: 39ºC SAT.O2: 90% Peripheral via was established to administer medications and a hydration plan, and low-flow oxygen therapy with a simple 4-liter nasal cannula was started. 0.9% saline solution is also administered as a hydration plan, paracetamol to reduce temperature, and oxygen therapy to improve hypoxemia. The most accurate tests to detect acute bronchitis in these patients were diagnostic tests, x-ray and sputum, physical examination, auscultation, slight mobilization of secretions at the hilar level. In conclusion, the most effective treatment for this disease in these patients is to rest and drink plenty of fluids and follow the treatment indicated by the treating physician.